Tear Fluid and Serum Vitamin D Concentrations in Unilateral Pterygium. Issue 2 (February 2021) - Örnek, Nurgül; Oğurel, Tevfik; Kısa, Üçler
Abstract : SIGNIFICANCE: Vitamin D has antiangiogenic, anti-inflammatory, and antifibrotic properties, which may play an inhibitory role on pterygium formation. Vitamin D concentration was measured in few studies, and contradictory results have been reported. There is no study investigating tear fluid concentration of vitamin D in pterygium patients. PURPOSE: This study evaluated tear fluid and serum vitamin D concentrations of pterygium patients in comparison with healthy controls. METHODS: Thirty-five (21 male, 14 female) patients with unilateral pterygium and 25 (18 male, 7 female) healthy controls were included in this case-control study. After full ophthalmic examination, blood samples were taken, and basal tear fluid was collected using glass microcapillary tubes. Tear fluid and serum vitamin D concentrations were analyzed using enzyme-linked immunosorbent assay and analyzed statistically. RESULTS: The mean ± standard deviation age of patients was 51.7 ± 16.7 years in the study group and 50.6 ± 18.7 years in the control group, respectively ( P = .82). The mean tear fluid vitamin D concentration was statistically significantly higher than the mean serum concentration in the study groups ( P < .0001). The mean tear fluid ( P = .76) and serum vitamin D concentrations ( P = .53) did not reveal statistically significant difference between patients and controls. There was no statistically significant difference for tear fluid vitamin D concentration between pterygium eyes and fellow eyes ( P = .93). The difference in concentrations was compared within the pterygium subgroups, and it was found that the mean serum vitamin D concentration trended toward lower values as the stage of pterygium increased, and the mean tear fluid vitamin D concentration trended toward higher values as the stage of pterygium increased, although these differences were not statistically significant (all, P > .05). CONCLUSIONS: Tear fluid and serum vitamin D concentrations do not seem to have a role in pterygium pathogenesis.